Feasibility study of power generation using a turbine mounted in aircraft wing - Krishna, K. Sri Vamsi; Prasad, Shiva; Vihar, R. Sabari; Babitha, K.; Veeranjaneyulu, K; D., Govardhan (International Journal of Engineering and Technology, 2018)
The main objective of this study is to increase the aerodynamic efficiency of turbine mounted novel wing. The main motive behind this work is to reduce the drag by attaining the positive velocity gradient and generate power by converting the stagnation pressure which also acts as emergency power source. By using the energy source of free stream air, Mechanical energy is converted into electrical energy. The obtained power is presented in terms of voltage generated at various angles of attack with different Reynolds number. Experimental analysis is carried out for NACA4415 airfoil at various angles with respect to free stream ranging from 0deg to 30deg from laminar to turbulent Reynolds number. The results were obtained using the research tunnel at IARE aerodynamic facility center. The aerodynamic advantage of this design in terms of voltage is 9.5 V at 35m/s which can be utilized for the aircraft on board power systems.